Sacred Rivals : Catholic Missions and the Making of Islam in Nineteenth-Century France and Algeria - Peterson, Joseph W. (Book collections on Project MUSE., 2022)
"Sacred Rivals focuses on French Catholic ideas about Islam and Arab-ness-"Catholic orientalism"-in the context of religious culture wars in France and missionary work in colonial Algeria. Relying on research from ten different public and private archives, the book tacks back and forth between the way the stereotype of "Islam" was used and abused in religious and political debates in French society; and fine-grained stories of actual missionary encounters with Muslims in Algeria, where missionaries and their potential converts came into intimate, daily contact. Bringing domestic French representations together with colonial realities of Islamo-Christian contact, this book uncovers how Catholic ideas about Islam influenced and were influenced by missionary experiences. Counter-intuitively, it was sometimes the most conservative Catholics who spoke most sympathetically of Muslim religiosity, because they felt embattled by the rise of secularization in France, optimistic about the sudden opportunity for Catholic missions in Algeria, and envious of the apparent piety and unity of Muslim society. By contrast, "liberal," mainstream Catholics-who loudly professed their respect for the liberty of Muslim consciences and hence their opposition to Catholic missions in French Algeria-were often quicker to denigrate Islam as backward, fanatical, and dangerously theocratic. As the century wore on, and as Catholics increasingly came to identify with France's more secular "civilizing mission," the conservatives' admiration for Islam would be eclipsed by a more racialized, colonialist orientalism. Disillusioned with the possibility of Muslim conversion and seeking an explanation for their failure, even missionaries in Algeria joined in with racially-coded attacks on "Arab" Islam"--